River to reservoir : geoscience to engineering - Corbett, P. W. M.; Owen, A.; Hartley, A. J.; Pla-Pueyo, S.; Barreto, Daniel (College teacher); Hackney, C.; Kape, S. J. (The Geological Society, 2019)
This volume presents a synthesis of research on the controls of dynamic changes to river systems, in particular under changing climatic conditions. The content covers both short engineering timescales and long geological timescales. The book will highlight the cross-disciplinary interest in rivers and their sediments and will interest geologists, geomorphologists, engineers and government agencies.
Keywords: Rivers.; Hydrogeology.; elektronické knihy; electronic books